2005
DOI: 10.1001/archopht.123.3.321
|View full text |Cite
|
Sign up to set email alerts
|

The US Twin Study of Age-Related Macular Degeneration

Abstract: Age-related macular degeneration (AMD) is the leading cause of irreversible blindness among older individuals in many parts of the world. The relative importance of genes and environment in the etiology of this major public health problem is not well understood.Objective: To investigate the impact of genetic and environmental factors.Participants: Living twins in the National Academy of Sciences-National Research Council World War II Veteran Twin Registry born between 1917 and 1927.Methods: Twins were surveyed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
134
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 379 publications
(145 citation statements)
references
References 56 publications
9
134
0
2
Order By: Relevance
“…In a study based on 406 twin pairs with 226 monozygotic and 280 dizygotic twins, Hammond et al [18] calculated a heritability of age-related maculopathy and late AMD of 0.45 and 0.81, respectively. This was confirmed by Seddon et al [20] based on the analysis of 840 elderly male twins including 210 monozygotic and 181 dizygotic complete twin pairs and 58 singletons, showing heritability rates for grade 3 and 5 AMD of 0.67 and 0.71, respectively.…”
Section: Genetic Studiessupporting
confidence: 62%
See 1 more Smart Citation
“…In a study based on 406 twin pairs with 226 monozygotic and 280 dizygotic twins, Hammond et al [18] calculated a heritability of age-related maculopathy and late AMD of 0.45 and 0.81, respectively. This was confirmed by Seddon et al [20] based on the analysis of 840 elderly male twins including 210 monozygotic and 181 dizygotic complete twin pairs and 58 singletons, showing heritability rates for grade 3 and 5 AMD of 0.67 and 0.71, respectively.…”
Section: Genetic Studiessupporting
confidence: 62%
“…Indeed, a higher concordance rate of AMD has been demonstrated in both study designs including monozygotic twins or relatives of AMD patients. Twin studies have strongly suggested underlying genetic factors in AMD, showing that the concordance of the disease was higher among monozygotic than dizigotic twins [15,16,17,18,19,20]. In a study based on 406 twin pairs with 226 monozygotic and 280 dizygotic twins, Hammond et al [18] calculated a heritability of age-related maculopathy and late AMD of 0.45 and 0.81, respectively.…”
Section: Genetic Studiesmentioning
confidence: 99%
“…These variants were identified using the xBrowse software to filter variants by the following stringent criteria: (1) had a minor allele frequency (MAF) of < 0.1% in the 1000 Genomes Project and Exome Aggregation Consortium (ExAC) databases, (2) belonged to a potentially damaging functional annotation class, (3) was predicted in silico to have a functional impact on protein function, and (4) followed the inheritance pattern of the disease within the family.…”
Section: Resultsmentioning
confidence: 99%
“…The disease affects the central region of the retina, resulting in progressive visual impairment and reduced quality of life. AMD is highly heritable and twin studies have shown that between 46% and 71% of phenotypic variance is explained by genetic factors 1,2 . Several environmental and genetic components contribute to its multifactorial etiology 2 .…”
mentioning
confidence: 99%
“…Age was observed to be the main risk factor for AMD in the Beaver Dam, Blue Mountains, and Rotterdam epidemiologic studies [3,4]. However, specific risk factors of AMD have been suggested or recognized, such as genetic allelic predisposition [5,6], female gender [7], hypertension and history of cardiovascular disease [8], smoking [9], high body mass index [10], and a diet rich in meat and lipids [11]. In developed countries, life expectancy has increased significantly during the past 20 years [12], but at the same time, exposure to many of the recognized environmental risk factors for AMD also increased during this period.…”
Section: Introductionmentioning
confidence: 99%